Sustainability of a privatized community-based animal health worker system in Mwingi district, Kenya - Rubyogo, Jean-Claude; Murithii, PM; Agumbah, G.J.O.; Obhai, G (Springer, 2005)
This paper describes a study on the sustainability of Community-based Animal Health Worker (CAHW) services in Mwingi District, Kenya. These services began in 1992 and were supported by the District Veterinary Authority (DVA) with assistance from the Integrated Food Security Programme Eastern (IFSP-E). Over time and using a process of participatory reviews with multiple stakeholders, the system evolved into a network of CAHWs. The study focused on CAHWs service sustainability and their relationships with other animal health service providers. A mutually beneficial and supportive arrangement existed between the CAHWs and Animal Health Assistants (AHAs), based on a private drug supply system, referral and backstopping support. The CAHWs derived sufficient income from their veterinary work to maintain their interest in the system. Seventy per cent of CAHWs were continuing to offer adequate animal health services 3 years or more after their initial training and the withdrawal of donor support. Ninety-five per cent of sampled CAHWs (n = 40) viewed their business as successful and expanding. Considering the agro-ecological and socio-economic conditions of the district, the CAHW system can be viewed as an initial stage in the process of extending quality private sector veterinary services.